2007
DOI: 10.1155/2007/46581
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Determination of Macrolide and Lincosamide Resistance in Group B Streptococcus Isolated from Vaginal-Rectal Swabs

Abstract: Objective. Our objective was to assess the ability of real-time PCR to predict in vitro resistance in isolates of group B streptococcus (GBS). Methods. The first real-time PCR assays for the genes known to confer resistance to erythromycin and clindamycin in GBS were developed. Three hundred and forty clinical GBS isolates were assessed with these assays and compared with conventional disk diffusion. Results. The presence of an erythromycin ribosome methylation gene (ermB or ermTR variant A) predicted in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
(19 reference statements)
2
2
0
Order By: Relevance
“…In addition, in current study, both erm and mef (A/E) genes were identified in erythromycin-resistant isolates, with erm (B) dominating. We observed a higher level of discordance between genotype and phenotype in S. pyogenes , and there were erm (B) genes in 9 erythromycin-susceptible isolates, as consistent with previous report in S. agalactiae (Dela Cruz et al, 2007 ) and SDSE isolates (Lu et al, 2016 ), hinting an alternate mechanism of resistance or a potential mutation in the 23S Rrna (Dela Cruz et al, 2007 ). Furthermore, 90.3% (421/466) harbored the erm (B) gene in S. pyogenes strains isolated from Beijing children (Liang et al, 2012 ).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, in current study, both erm and mef (A/E) genes were identified in erythromycin-resistant isolates, with erm (B) dominating. We observed a higher level of discordance between genotype and phenotype in S. pyogenes , and there were erm (B) genes in 9 erythromycin-susceptible isolates, as consistent with previous report in S. agalactiae (Dela Cruz et al, 2007 ) and SDSE isolates (Lu et al, 2016 ), hinting an alternate mechanism of resistance or a potential mutation in the 23S Rrna (Dela Cruz et al, 2007 ). Furthermore, 90.3% (421/466) harbored the erm (B) gene in S. pyogenes strains isolated from Beijing children (Liang et al, 2012 ).…”
Section: Discussionsupporting
confidence: 91%
“…Yet another study in Ireland also reported that there were no recognized resistance mechanisms found in GBS isolates resistant to erythromycin [29] . A similar finding was reported from another study in the USA where one isolate showed sensitivity to erythromycin and resistance to clindamycin; however, the isolates did not carry any of ermB , ermTR , or mefA genes [30] . Hence, these findings would deviate the focus of attention from existing knowledge in search of other mechanisms that may be present for reported resistance.…”
Section: Discussionsupporting
confidence: 88%
“…Hence, these findings would deviate the focus of attention from existing knowledge in search of other mechanisms that may be present for reported resistance. A probable mechanism may be a mutation in the 23S rRNA which has been reported in S. pneumoniae for macrolide resistance [30].…”
Section: Discussionmentioning
confidence: 99%
“…These techniques include the use of chromogenic agar/broth and nucleic acid amplification technology (NAAT) [3, 4]. While both of these techniques have been employed in screening for antenatal GBS colonization, the Centers for Disease Control and Prevention still recommend that culture be performed [5].…”
Section: Introductionmentioning
confidence: 99%